PENGARUH KINERJA FRONT OFFICE TERHADAP KEPUASAN TAMU DI VINILA VILLA NUSA DUA - Ni Nyoman Menuh; I Gede Wisnu Herikesha (Forum Manajemen, 2020)
With the management of professional human resource management, it is hoped that employees can perform well in serving guests in order to create satisfaction from these guests. Besides not missing the rules set by management. However, the purpose of this study was to analyze the effect of employee performance, especially in the Front Office towards the satisfaction of guests staying at Vinila Villa Nusa Dua. The type of data used in this study is qualitative data and quantitative data, with data sources namely premier data. The method of data collection is done by distributing questionnaires in the form of guest comments to respondents, namely guests who stay overnight, while the data analysis techniques used are: classical assumption test, simple linear regression and hypothesis testing. The results showed that the Front Office Performance significantly affected the satisfaction of guests staying at Vinila Villa Nusa Dua